BIOLOGICAL STUDY OF TWO SPOTTED SPIDER MITE Tetranychus sp. (ACARI: TETRANYCHIDAE) ON THREE LEAF PHASES OF MUNG BEAN AND ADZUKI BEAN FOR MITE MASS REARING - Retno Dyah Puspitarini; Arif Danu Satria; Ludji Pantja Astuti (AGRIVITA, Journal of Agricultural Science, 2013)
Two-spotted spider mite (TSM) Tetranychus sp. is one of prey mites for phyotoseiid mite mass rearing.  Based on previous research that TSM population developed well on Mung bean (Vigna radiata) and Adzuki bean (V. angularis) as host plants, confirmed growth and development of TSM on both beans. Research was aimed to observe biology of TSM on three phases of Mung bean and Adzuki bean leaf such as at primary leaf unrolled completely (V1), at the 1st trifoliate unrolled completely (V2), and at the 2nd trifoliate unrolled completely (V3). Pre adult stadia, life cycle, male and female longevity, female fecundity of TSM, and trichome density were observed on petri dishes contained each leaf phase of beans.  Result showed that three leaf phases of beans did not influence significantly in all biological variables, except fecundity. TSM fecundity was the highest on V3 phase of Mung bean (86.90). Trichome density on Mung bean leaf surface per mm² was lower than Adzuki bean. Trichome density of upper leaf surface of V3 phase of Mung bean (10.53) and Adzuki bean  (3.07) were lower than V1 (13.20; 12.40) and V2 phase (6.20; 5.27). V3 phase of Mung bean was most suitable for TSM mass rearing.Key words:  fecundity, leaf phase, mass rearing, trichome density, two-spotted spider mite